Fabrication and Evaluation of Polydimethylsiloxane-La2O3 Composites-Based Flexible Capacitance Pressure Sensors’ Parameters and Applications - Soly Mathew; Krishnamoorthi Chintagumpala (IEEE Access)
Flexible capacitance pressure sensors (fCPS) with high sensitivity, wide linear working range, fast response and recovery times, low hysteresis, and long durability with stable output are very much needed for many physical sensor applications. For flexibility sensors both capacitor plates and dielectric sandwich layer in parallel plate capacitor (PPC) geometry should be flexible with low elastic modulus (E) with high tensile break point. For this purpose, many researchers were used flexible polymer sheet with surface conductive material coating as a flexible capacitor electrodes, and elastomer composites as dielectric sandwich layers. Capacitance (C) of a PPC sensor is C= $ε \frac {A}{D}$ , here $ε $ is dielectric permittivity of sandwich layer, A is effective area of PPC electrode plates, and D is distance between the electrode plates. Here change in capacitance under applied pressure is induced by change in $ε $ as well as D. Flexible dielectric elastomer composites (DECs) with high dielectric constant ( $ε _{\text {r}}$ ) were prepared by adding 0, 0.45, 0.90, & 1.34 mass% of relatively high dielectric La2O3 ceramic nanoparticles as fillers to polydimethylsiloxane (PDMS) matrix. The DEC were spin coated to make 0.2 mm thick films to use in PPCs. Four fCPS were fabricated using conductive silver epoxy coated polyethylene terephthalate (PET) substrates (0.125 mm thickness) for PPC electrodes and 0.2 mm thick DECs as sandwich layers. Sensitivity of the fCPS increases with La2O3 filler content. Among the four fCPS studied here, fCPS with 1.34 mass% La2O3 DEC shows highest sensitivity of 23.77 pF/kPa, linear working range in 0–2.56 kPa, response and recovery times of 123 & 126 ms, negligible hysteresis in 0-128 kPa range, and long durability with stable output. Compressive and tensile strain sensing capabilities of this sensor was tested in the real time applications.